Diopatra (Annelida: Onuphidae) diversity in European waters with the description of Diopatra micrura, new species - Pires, Adília; Paxton, Hannelore; Quintino, Victor; Rodrigues, Ana Maria (Zootaxa, 2010)
This study describes a new species of the genus Diopatra Audouin and Milne-Edwards, 1833. Diopatra micrura sp. nov., was found on the western and the southern coast of Portugal and can be distinguished from other Diopatra species by a characteristic striped colour pattern of the antennae and palps. Other diagnostic morphological characteristics include ventral parapodial lobes, crescentic nuchal organs, ceratophores with 12–15 rings, and subacicular hooks from chaetigers 8–13. This species was found mainly in fine or very fine sand with variable fines content, from the intertidal region up to 50 meters depth. Molecular studies of mitochondrial DNA genes 16S rDNA and COI confirmed the distinction of D. micrura sp. nov., from other European Diopatra species. The percentage of nucleotides divergence between the new species and D. neapolitana and D. marocensis was respectively 16% and 17% for COI and 12% and 15% for 16S. The nucleotide sequence for the 16S gene was always the same in all specimens of D. micrura and two haplotypes were found for the COI gene. The discovery of D. micrura sp. nov., brings the number of Diopatra species known from Portugal to three and from Europe to four; a key to the four species is provided.